(untitled) (Revista revoluciones, 2021)
The present research work has the purpose of analyzing the historical development of the uprising of the caudillo Pedro Vilcapaza Alarcón in the province of Azángaro: 1780 - 1782, who was the most important revolutionary character of the Puno highlands who was characterized by fighting in bloody battles against the oppression of the Spanish. In this way, through documentary review and content analysis, it can be determined that the extraordinary time of his death, of his glory and the desire for emancipation in the southern regions, made him one of the most representative cadillos on earth. indigenous. Thus, Azángaro turned out to be the seat of the rebellion of one of the most important historical events of the colonial era, a region that provided its people with masses determined to fight for freedom and to offer leaders worthy of immortality.